Modernist Waterscapes Water, Imagination and Materiality in the Works of Virginia Woolf - Dirschauer, Marlene (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This deeply thoughtful phenomenological study makes a welcome move from psychology to poetics in its original and illuminating account of Woolf's imaginative engagement with 'waterscapes'. Ranging over all the forms of Woolf's writing, Dirschauer contributes significantly to recent ecocritical readings of Woolf, beautifully mapping a network which encompasses English Romantic poets and Woolf's contemporaries." - Mark Hussey, Distinguished Professor Emeritus, Pace University, USA "In Modernist Waterscapes Marlene Dirschauer has captured the complexity, fullness, wonder, and fluid power of Woolf's writing....This is a profound and delightfully illuminating study of Woolf's immersion in the literary past as she creates radically new aesthetic forms that shape human connections with the vast web of the biosphere and its natural forces. A necessary new book for anyone interested in Virginia Woolf." - Louise Westling, Professor Emerita of English and Environmental Studies at the University of Oregon, USA This book identifies water as the key element of Virginia Woolf's modernist poetics. The various forms, movements, and properties of water inspired Woolf's writing of reality, time, and bodies and offered her an apt medium to reflect on the possibilities as well as on the exhaustion of her art. As a deeply intertextual writer, Woolf recognised how profoundly water has shaped human imagination and the landscape of the literary past. In line with recent ecocritical and ecofeminist assessments of her works, this book also shows Woolf's attraction to water as part of an indifferent nature that exists prior to and beyond the symbolic. Through close analyses that span the whole of Woolf's oeuvre, and that centre on the metaphorical and the material voices of water in her works, Modernist Waterscapes offers a fresh perspective on a writing that is as versatile as the element from which it draws. The monograph addresses students and scholars working in modernist studies and Woolf studies in particular. Marlene Dirschauer holds a PhD in Comparative Literature. Currently, she works as Research Fellow at the University of Hamburg, Germany. Her research interests are English modernism as well as religious writings of the early modern era.
1. Introduction: Virginia Woolf's Modernist Waterscapes -- 2. Aqueous Affinities: Woolf, Bachelard and the English Romantic Poets -- 3. 'How It Floats Me Afresh': Water in Woolf's Early Experimental Fiction -- 4. The Fluid Texture of Time: To the Lighthouse, Mrs. Dalloway, Orlando, The Waves -- 5. 'The Obscure Body of the Sea': Female Bodies, Water and Artistic Creation from The Voyage Out to The Waves -- 6. 'Floating Down a River into Silence': Water in Woolf's Later Works -- 7. Conclusion. .
Keywords: Literature, Modern -- 20th century; European literature; Ecocriticism; Space; Culture; Sex; Literature -- Aesthetics; Twentieth-Century Literature; European Literature; Ecocriticism; Space and Place in Culture; Gender Studies; Literary Aesthetics